Absenteísmo por licença médica em servidores de uma Instituição Federal de Ensino Superior em Minas Gerais - Batista, Iracema (2014)
In Brazil, much has been published on the nature of sickness absence of civil servants employed in federal institutions of higher education, but so far, there are few researches that used for such purposes the data base of the Integrated Administration System of Human resources-SIAPE. This study aimed to identify possible diferences between sickness absence of civil servants employed in the health sector and those working in other sectors of a federal institution of higher education located in Minas Gerais, with a corresponding population to 4011 servers.This cross-sectional study, with data collected from the webpage Siapnet health module, includes 1.860 sickness absence for treatment of the server and for sick family care; 1.318 of these sickness absence referred to servants of the health sector (group I) and 542 to servants of other sectors (group II), all of both sexes and holding positions compatible with 2nd and 3rd degree education. These sickness absence were granted between January and June 2012.We classified the diagnosis of the cause of morbidity in accordance with ICD 10. The statistical evaluation included descriptive analysis of the sample. We used the Kolmogorov-Smirnov test to ensure the normality of data. We employed the Mann-Whitney U-test to evaluate the difference between medians, and to verify the associations between variables statistical Pearson s chi-square test or the Binomial test were used. We adopted a significance level of 5% (p ≤ 0,05) for the analyses. In the two groups we investigated, the highest sickness absence rates occured in Group I, among females, and in the 40 to 50 age group. In both groups, were characterized days away with short duration (1 to 14 days). Musculoskeletal and connective tissue disorders are the most frequent causes of sickness absence in the Group I; the factors that are determinants of health, the contact with health services and the respiratory diseases were the main causes of sickness absence in Grupo II. The results presented in this study confirm the health sector, female, aged between 40 and 50 years as predictors of risk of sickness absenteeism factors, as well as increased frequency of musculoskeletal and connective tissue diseases on servers in the health area, tendency corroborated in other studies.